1976
DOI: 10.3109/10731197609118655
|View full text |Cite
|
Sign up to set email alerts
|

Animal Experiments with Biogalvanic and Biofuel Cells

Abstract: Animal experiments with biogalvanic cells have demonstrated that an average power of 80 muW can be derived continously for at least 2 years. There is a further scope to stabilize the power at 100 muW for considerable longer periods so that the chances of cardiac pacing with biogalvanic power have become bright. However, large scale efforts are necessary in in establishing the statistical reliability and the secured performance which are expensive and time consuming. Animal experiments with biofuel cells are st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…Mediation by the hexacyano-complexes of iron, 131,132 cobalt, and ruthenium has been extensively studied. [133][134][135] Of these, the Fe(CN) 6 3-/4-couple is used in home blood-glucose monitoring strips.…”
Section: Inorganic Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mediation by the hexacyano-complexes of iron, 131,132 cobalt, and ruthenium has been extensively studied. [133][134][135] Of these, the Fe(CN) 6 3-/4-couple is used in home blood-glucose monitoring strips.…”
Section: Inorganic Mediatorsmentioning
confidence: 99%
“…After 40 years of research, there is not a single biofuel cell in use. Originally, the biofuel cells were intended to power cardiac assist devices ("artificial hearts"), 2,3 then cardiac pacemakers, [4][5][6] then to supply electrical power to homes or electrical grids by electrooxidizing glucose in, or derived of, wastes. [7][8][9] The earliest studies already identified insurmountable power density and stability associated limitations, but these were not recognized by all investigators.…”
Section: Exclusion Of Studies On Glucose Electrooxidizing Anodes Of Cmentioning
confidence: 99%
“…Research in the field of implantable direct glucose fuel cells dates back to the early seventies [3,4]. These early efforts were motivated by the short life-time of the zinc/mercury oxide batteries at that time.…”
Section: A Historical Interludementioning
confidence: 99%
“…In order to circumvent this chemical short-circuit, we chose a special electrode arrangement, originally proposed by Weidlich et al [4] (Fig. 2).…”
Section: One-compartment Design and Self-organizationmentioning
confidence: 99%
See 1 more Smart Citation